High-speed lightwave communication ICs based on III-V compoundsemiconductors. - Sano, E.
Ultra-high-speed ICs are one of the keys to achieving large-capacity lightwave communications systems. This article reviews advances in lightwave communication ICs based on III-V compound semiconductors developed to obtain next-generation 40-Gb/s/wavelength channel systems
Keywords: 40 Gbit/s.; III-V compound semiconductors; High-speed lightwave communication IC; Large-capacity lightwave communications systems